2012
DOI: 10.1002/cphc.201200072
|View full text |Cite
|
Sign up to set email alerts
|

Trap States in TiO2 Films Made of Nanowires, Nanotubes or Nanoparticles: An Electrochemical Study

Abstract: The presence of electronic traps in nanoporous TiO(2) electrodes has been studied by cyclic voltammetry in aqueous media. These simple measurements allow us to map the density of states, providing evidence for the presence of a relatively small number of discrete electron traps at the band gap. We have taken advantage of the variety of TiO(2) synthetic procedures that lead to well-defined morphologies (such as nanowires, nanocolumns, nanotubes, and nanoparticles) of anatase and rutile to investigate the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
103
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 70 publications
9
103
0
1
Order By: Relevance
“…In agreement with the previous results, [11] the pair of peaks ascribed to grain boundaries [47] appearing at À0.8 V (TiO 2 ) and À0.95 V (NiTiO 3 ) are highly promoted and in the case of anatase, they are clearly displaced toward more positive potential values after the electrochemical pretreatment. In agreement with the previous results, [11] the pair of peaks ascribed to grain boundaries [47] appearing at À0.8 V (TiO 2 ) and À0.95 V (NiTiO 3 ) are highly promoted and in the case of anatase, they are clearly displaced toward more positive potential values after the electrochemical pretreatment.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with the previous results, [11] the pair of peaks ascribed to grain boundaries [47] appearing at À0.8 V (TiO 2 ) and À0.95 V (NiTiO 3 ) are highly promoted and in the case of anatase, they are clearly displaced toward more positive potential values after the electrochemical pretreatment. In agreement with the previous results, [11] the pair of peaks ascribed to grain boundaries [47] appearing at À0.8 V (TiO 2 ) and À0.95 V (NiTiO 3 ) are highly promoted and in the case of anatase, they are clearly displaced toward more positive potential values after the electrochemical pretreatment.…”
Section: Resultssupporting
confidence: 92%
“…This is probably linked to the initial larger recombination existing at NiTiO 3 electrodes. In this regard, there are few publications that have shown that it exists an exponential relation between the charge corresponding to the grain boundary peak and the electrolyte pH [46,47] and these traps have been linked to recombination processes. [11] This result clearly points to the key role of pH in the electrochemical doping process.…”
Section: Resultsmentioning
confidence: 99%
“…20,26,27 It is reasonable to think that TiO 2 can be negatively charged if electrons are trapped in band gap states. Moreover, it has long been realized that electron trapping in band gap states can induce proton (or other cation ions) charge compensation uptake (call ETPU).…”
Section: Occurrence Of Etpumentioning
confidence: 99%
“…10 In addition, these states may act as recombination sites exerting a further deleterious impact on the photocurrent. 32 …”
Section: Introductionmentioning
confidence: 99%